2018
DOI: 10.1155/2018/6150861
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Hepatitis C Association with Diabetes Mellitus and Cardiovascular Risk in the Era of DAA Therapy

Abstract: Patients with chronic hepatitis C have both higher prevalence of diabetes mellitus type 2 (T2DM) and increased cardiovascular risk compared to never infected people. Sustained viral response (SVR) achievement led to decreasing incidence and prevalence of T2DM during the interferon era of HCV treatment. Currently, direct-acting antiviral drugs (DAA) are the gold standard for treating HCV infection, while yielding SVR in nearly all patients. In chronic HCV patients with T2DM (prediabetes most likely too), DAA th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
61
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(67 citation statements)
references
References 84 publications
3
61
0
3
Order By: Relevance
“…It has been recently shown that DAAs improve metabolic balance in CHC patients by exerting beneficial effects on fasting glucose, glycated haemoglobin and hypertension …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been recently shown that DAAs improve metabolic balance in CHC patients by exerting beneficial effects on fasting glucose, glycated haemoglobin and hypertension …”
Section: Discussionmentioning
confidence: 99%
“…These changes may result in a large number of benefits even in older ages such as reduction of polypharmacotherapy and cardiovascular risk and finally in improvement of quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…58 Hypolipidemia during viremic status can be reversed to deteriorate lipid profiles after DAA therapy. 59 An increase in the small dense low-density lipoprotein cholesterol level corresponding to increased carotid intima-media thickness 1 year after DAA therapy has been reported. 60 Attention should be paid not only to liver-related complications but also to the extrahepatic consequence of cardio-cerebrovascular disease in the post-SVR period.…”
Section: Extrahepatic Manifestationsmentioning
confidence: 98%
“…Chronic hepatitis C (CHC) virus infection is a major cause of liver cancer and cirrhosis. In addition, some studies have indicated that patients with CHC have both higher prevalence of type 2 diabetes and increased cardiovascular risk compared to those who have never been infected [1,2]. Globally, an estimated 71 million people have CHC, which is caused by the hepatitis C virus (HCV), a blood borne virus.…”
Section: Introductionmentioning
confidence: 99%
“…The World Health Organization has developed a global health strategy to eliminate hepatitis C by 2030 [4], and the Taiwanese government also launched an elimination goal by 2025 [3]. In addition, previous literature confirmed that DAA treatment is not only beneficial for HCV clearance but is also associated with better fasting glucose and controlled glycated hemoglobin levels and improved cardiovascular function [2,11].…”
Section: Introductionmentioning
confidence: 99%